An experience on participatory management of biodiversity with Amazonian communities - Álvarez, José (2012)
For the past 10 years, the Instituto de Investigaciones de la Amazonía Peruana (Peruvian Amazon Research Institute) - IIAP, Nature and Culture International (NCI), together with local communities, the Regional Government of Loreto, and other private organizations, have been developing a community co-management model for the Amazonian biodiversity, with very promising results. In the three basins where such co-management projects were implemented (Tahuayo, Yanayacu and Nanay), we are seeing a concrete evidence of reversals in the processes of degradation of resources and ecosystems. In each of these basins, a significant reduction in logging, illegal fishing and hunting, and destructive harvesting methods of resources can be found as a directresult of the co-management model. Significant economic improvements to local communities are achieved mainly due to the commercialization of value-added biodiversity products, as well as the recovery of fisheries, wildlife and other resources. The main principles of this model are : (1) productive conservation (conservation as a business, that is to recover flora and fauna resources and their management in ways that allow income generation); (2) adaptive management (simple management actions designed and progressively adopted by the communities and accompanied with technical support); (3) eco-systemic approach (conservation of large landscapes, especially watersheds, prioritized ecological processes such as fish’s seasonal migrations, and conservation of source areas); (4) making use of standing forest (to prioritize revenues from sustainable use of forest vs. cutting down the forest); (5) participation of all stakeholders from the organized and properly consulted local communities, to private enterprises, public institutions and all decision-makers; (6) development of complete productive chains with value-added biodiversity products and insertion in markets; (7) adaptive management (progressive adjustment of institutions and norms according to communities’ capacities).